Terapi Senam Aerobic Low Impact dengan Halusinasi Pendengaran: Suatu Studi Kasus - Makmur; Sri Novitayani (Jurnal Riset Keperawatan dan Kesehatan, 2026)
Background: Hallucinations are one of the positive symptoms of schizophrenia and commonly occur as auditory hallucinations. Inadequately managed hallucinations may increase the risk of violent behavior, social isolation, suicide attempts, low self-esteem, and self-care deficits. Objective: This case study aimed to provide comprehensive nursing care through low-impact aerobic exercise therapy for a patient experiencing hallucinations at Aceh Mental Hospital. Methods: The patient received nursing implementation strategies and low-impact aerobic exercise therapy for 3 days, consisting of 6 sessions with a duration of 30 minutes per session. Evaluation was conducted using the Auditory Hallucination Rating Scale (AHRS). Results: The findings showed a reduction in the AHRS score from 23 (severe category) to 18 (moderate category). Improvements were observed in the frequency of voices, duration of whispers, intensity of voices, disturbances caused by voices, and control over voices. In addition, the patient reported feeling happier, more comfortable, calmer, and more motivated after participating in the therapy. Conclusion: Low-impact aerobic exercise therapy was effective in reducing the severity of auditory hallucinations and improving the patient's psychological well-being. This intervention may be recommended as a supportive nursing therapy for patients experiencing hallucinations.